Interpretation of age based on the scales of lacustrine Salmonidae, the common whitefish (Coregonus sp.) and the arctic char (Salvelinus alpinus) - Hamelet, Valérie; Goulo, Chloé; Marchand, Frédéric (INRAE, 2022)
Knowledge of the growth and structure in terms of age of a fish population is very important when focusing on the dynamics of the populations exploited and their management. The Colisa Biological Resource Centre provides this expertise based on different samples (scales, otoliths, gill covers, etc.). The aim of this article is to describe this interpretation of age based on the scales of lacustrine Salmonidae species, the common whitefish (Coregonus sp.) and the arctic char (Salvelinus alpinus). La connaissance de la croissance et de la structure en âge d’une population de poisson est particulièrement importante lorsque l’on s’intéresse à la dynamique des populations exploitées et à leur gestion. Le Centre de Ressources Biologiques Colisa assure cette expertise à partir de différents échantillons (écailles, otolithes, opercules …). L’objectif de cet article est de décrire comment se fait cette interprétation de l’âge à partir des écailles sur des espèces de salmonidés lacustres, le corégone (Coregonus sp.) et l’omble chevalier (Salvelinus alpinus).